Examining the implementation of extended producer responsibility within the palm oil industry: Challenges and opportunities for sustainable practices - Kurniawan, A Azis; Nahriyah, Muflihatun (Applied Environmental Science, 2025)
Background: Indonesia, as the world's leading palm oil producer, significantly contributes to the global supply and national GDP. However, the industry's expansion has led to increased plastic waste generation, exacerbating environmental and health concerns due to inefficient waste management. Extended Producer Responsibility (EPR) has been proposed as a strategic solution to improve sustainability in the sector. Method: This study conducts a systematic review of sustainability reports from Indonesian palm oil companies, analyzing corporate approaches to plastic pollution, sustainable packaging, and EPR. Data were collected from company websites and linked packaging-related sections, followed by a content analysis to assess commitments to these key areas. Findings: The analysis reveals a divide within the sector: while half of the major companies acknowledge plastic pollution in their reports, the other half lack awareness or action. Sustainable packaging initiatives remain insufficient to meet Indonesia’s target of reducing plastic usage by 30% by 2029. Additionally, corporate commitment to EPR is limited to only a small portion of the industry. Conclusion: The study highlights the need for stronger regulatory enforcement and corporate accountability in addressing plastic waste management. A broader adoption of EPR and sustainable packaging practices is crucial for the palm oil sector to align with national and global environmental goals. Novelty/Originality of this Study: This study provides a critical assessment of plastic waste management in the Indonesian palm oil sector, offering insights into corporate sustainability commitments. By evaluating EPR adoption and sustainable packaging practices, it identifies gaps and areas for policy and industry improvement.